Heat and temperature metacognition awareness inventory: A confirmatory factor analysis - Moh. Irma Sukarelawan; Dwi Sulisworo; Jumadi Jumadi; Heru Kuswanto; Siti Anisatur Rofiqah (International Journal of Evaluation and Research in Education (IJERE), 2021)
This cross-sectional study aimed to validate students' metacognition awareness inventory in Heat and Temperature material. A total of 167 public senior high school students in Yogyakarta, Indonesia were selected through convenience sampling technique. The heat and temperature metacognition awareness inventory (HeTMAI) inventory consists of six factors, namely: 1) Knowledge of cognition; 2) Planning; 3) Monitoring; 4) Evaluation; 5) Debugging; and 6) Information management. HeTMAI used a 5-point Likert scale. The data was analyzed using the confirmatory factor analysis (CFA) method through the Maximum Likelihood approach. All statistics were found to meet acceptance values. The four GOF indices (χ2/df=2.36, CFI=0.97, TLI=0.97, and SRMR=0.06) have supported the fit of the six-factor HeTMAI model. Standardized factor loading (SFL), construct reliability (CR), average variance extracted (AVE) and discriminant values provide evidence that HeTMAI has sufficient convergent and discriminant validity. Cronbach's alpha value of 0.96 indicated HeTMAI has very adequate evidence of reliability.